PERAN LITERASI DALAM MENDORONG PERILAKU SEHAT MASYARAKAT: SYSTEMATIC REVIEW - Rubiyanta; Widiyanto, Aris; Anantayu, Sapja (Forind Press, 2025)
Literacy plays an important role in shaping healthy behaviors in society and serves as one of the strategic approaches in health promotion. This study aims to systematically examine empirical evidence on the role of literacy in encouraging healthy behaviors in the community. The method used was a systematic review referring to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Article searches were conducted in the PubMed, Scopus, ScienceDirect, Google Scholar, and GARUDA databases, covering the publication period from 2019 to 2025. A total of four articles were analyzed; these were primary studies with experimental and observational designs that examined health literacy or digital health literacy and healthy behavior outcomes. From the selection process, four articles met the inclusion criteria. The results of the review showed that all studies reported a positive relationship between literacy and healthy behaviors, including healthy dietary patterns, physical activity, health information–seeking behavior, and health promotion behaviors. Health literacy and digital health literacy play a role in improving individuals’ ability to understand, evaluate, and appropriately apply health information, which is associated with changes toward healthier behaviors. The conclusion of this review emphasizes that strengthening literacy needs to be integrated into health promotion programs to enhance the effectiveness of efforts to improve healthy behaviors in the community.